Measuring Stereotype Threat at Math and Language Arts in Secondary School: Validation of a Questionnaire - Bedyńska, Sylwia; Rycielski, Piotr; Jabłońska, Magdalena (Frontiers in Psychology, 2021)
Stereotype threat arises when a negative stereotype about one’s group is activated. It affects students’ achievement and interest in a particular academic domain e.g. girls at math or boys at language arts. Hence it is important to assess the level of stereotype threat at school in order identify students vulnerable to its negative consequences. This study devised and validated two parallel versions of Stereotype Threat at School scale: for girls in mathematics and for boys in language arts in a nationally representative sample of Polish secondary school pupils (N = 1241; 13-16 yrs). The results of a confirmatory factor analysis (CFA) in a complex sample approach showed one general factor. Furthermore, a multiple-group CFA confirmed metric invariance and partial scalar invariance. The variances for boys and girls were also equal. This suggests that the construct of stereotype threat is similarly conceptualized by both genders despite different domains. Finally, the comparison of means of latent variables revealed a higher level of stereotype threat among boys in language domain than girls in mathematics. Possible theoretical and practical implications are discussed.